Analisis Desain Vertikal Wind Turbin Dengan Air Foil Naca 0016 Modified Menggunakan Software Ansys 14.5 - Irawan, Jehan Rosadi; , Nur Aklis, S.T., M.Eng; , Wijianto, ST, M.Eng (2016)
The purpose of this study was to determine the performance of blade vertical wind turbine-type Darrieus-H with airfoil naca 0016 modified by varying the amount of the blade and the angle of attack by using the software Ansys Moving Reference Frames (MRF), and determine the influence of pressure distribution, velocity, comparison of the coefficient of lift (CL), the coefficient of drag (CD) and to know the results of the power coefficient (Cp), solidity number of blades on a vertical wind turbine. The study was conducted by using dimensional geometry with modified airfoil naca 0016, verify the number of simulated blade includes blade 2, 3 and 4 to parameter variations of angle of attack -100, 00, 100, the experiment begins with making the model number of the blade and make the simulation area with a length of 4000 mm, width 8000 mm and 1920 mm circle using SolidWorks interface, after the meshing using size with a minimum spacing of 0.005 and a maximum spacing of 0.05 m and the results of calculations performed Ansys software. There is also research that will be conducted using 2D steady-state simulation solver using Moving Reference Frames (MRF) on ANSYS fluent. The results showed that each of the blade and the angle of attack of wind turbine vertical experience speeds and pressures are different and produce different style, the design of vertical axis wind turbine-type Darrieus-H with airfoil naca 0016 modified can be seen below, the airfoil shape is great to make great velocity on the side of the airfoil, and generate tremendous pressure on the front end of the airfoil, can be influenced at an angle of attack that will cause huge turbulence flow. The results of the design of wind turbines capable of generating power coefficient value at the blade 2 with the angle of attack equal to 0,531 -100, 00 at 0.555 and 100 amounted to 0.581, for the blade 3 with angle of attack for 0,313 -100, 00 for 0,367 and 100 amounted to 0.278, the blade -100 4 with the angle of attack of 0.329, 0.406 and 00 of 100 of 0.461. And to the results of the solidity of the blade to the blade number 2 for σ = 1.9625 and for blade 3 for σ = 2.8875 for the blade 4 of σ = 3.85 with a wind speed of 3 m / s. Keywords: The amount of the angle, angle of attack, Cl, Cd, Cp and solidity